Timing over occurrence: a systematic literature review of how sexual activity and masturbation affect athletic performance - Maxi Moleong; Fredrik Alfrets Makadada; Fadli Ihsan (Indonesian Institute For Counseling, Education and Therapy, 2026)
The effects of sexual activity and masturbation before exercise or competition on athletic performance remain unclear. This systematic review examined their short and long-term effects on physical performance and physiological responses, proposed underlying mechanisms, and methodological limitations in the existing literature. A systematic search of the Scopus database was conducted according to PRISMA 2020 guidelines, identifying 281 records. Following title and abstract screening and application of predefined eligibility criteria, 50 articles were included in the review. Of these, 10 directly investigated the relationship between sexual activity or masturbation and athletic performance. The relevant evidence was synthesized thematically using Braun and Clarke’s framework. A meta-analysis was not performed because of substantial heterogeneity in study outcomes and measures. Overall, sexual activity or masturbation performed more than two hours before exercise or competition did not appear to significantly affect strength, endurance, physical performance, or reaction time. Findings for shorter intervals were inconsistent. Psychological readiness and sleep quality may influence performance, while testosterone fluctuations, autonomic arousal, and perceived exertion were the most frequently proposed physiological mechanisms. However, small sample sizes, reliance on self-reported data, and inconsistent definitions of sexual activity limited the interpretation of causal relationships. Current evidence does not support strict abstinence from sexual activity or masturbation before competition. Individualized, evidence-based recommendations may be more appropriate for athletes. Further research using larger and more diverse samples, standardized definitions, objective measurements, and rigorous study designs is needed to clarify the relationship across different sports and levels of competition.